Optimal TMD design for floating offshore wind turbines considering model uncertainties and physical constraints. (1st January 2022) - Verma, Mohit; Nartu, Manoj Kumar; Subbulakshmi, A.
Abstract: The wind resources can be efficiently tapped using floating offshore wind turbines (FOWTs). However, the increased loading due to coupled action of wind and waves can affect the efficiency of the wind turbines. Structural control utilizing tuned mass damper (TMD) is an effective solution for response control of FOWT. An efficient framework for optimal design of TMD is presented in this paper. The main features of the proposed framework are: (1) The design of TMD is cast in the form of feedback control problem. The parameters of the TMD like stiffness and damping acts like a static-controller, whose gains are evaluated such that the performance specifications (described by a certain norm of the FOWT and/or TMD responses) are minimized, (2) the performance specifications are reduced to a convex program using linear matrix inequalities (LMIs), (3) the optimization problem is solved using an iterative LMI procedure, (4) the design procedure incorporates model uncertainties and, (5) the physical constraints (like TMD relative displacement) can also be incorporated by formulating design problem as multi-objective optimization. The optimal TMD design is illustrated for a case where TMD is installed in nacelle. Finally, the nonlinear dynamic response of the FOWT with the optimized TMD is evaluated using aero-hydro-servo-elastic analysis. Five different load cases with varying wind and wave loading are considered for simulations. The performance assessment is carried out in terms of structural response, damage equivalent fatigue loads and fluctuations in power generation. The designed TMDs are found to be effective for all the load cases. The proposed methodology is found to be effective for optimal tuning of the TMDs for response control of FOWT. Highlights: The problem of finding optimal tuned mass damper for floating offshore wind turbine is cast as feedback control problem. The optimization problem is formulated for different scenarios of TMD design (including model uncertainties and physical constraints). The optimization problem is solved using an iterative LMI procedure utilizing a combination of convex and metaheuristic algorithms. The performance of the designed TMDs is assessed in terms of structural response, generator power fluctuations and shaft fatigue loads. The designed TMDs are found to be effective for different load cases.